(untitled) (Altre Modernità, 2012)
This essay discusses the modern novel’s attempt to create edenic spaces of natural innocence. It focuses on two French novels, La Faute de l’Abbé Mouret by Emile Zola (1875) and Le Mariage de Loti by Pierre Loti (1880), which both unsuccessfully try to build an edenic chronotope : a vegetal Paradise where time stops being a source of distruction, and where life seems to recover its lost signification. The analysis of these narratives will show that the construction of this kind of space has become, in the modern novel, a difficult and contradictory operation. Moreover, this renewed natural Eden appears incapable of containing the plot : it closes up on itself , expelling the heroes who inhabited it and rejecting them into the conflictual and incoherent space of Culture to which they belong. This unsuccessful construction leads the narratives to a contradictory representation of Nature, which becomes an uncanny space where the dark figures of the unconscious reveal the unsatisfactory illusion of the edenic chronotope. In this respect, these two narratives significatively rejoin the literary model which will dominate the representation of Natural spaces in the European novel by the end of the nineteenth century.